Comedo-like openings in melanoma - Bruno Simão dos Santos; Lucia Helena Soares Ribeiro; Eloisa Leis Ayres; Enoi Aparecida Guedes Vilar (Sociedade Brasileira de Dermatologia, 2014)
We describe a case of melanoma with the presence of comedo-like openings at dermoscopy. These structures, typical of seborrheic keratosis, represent an uncommon finding in melanoma. We emphasize the importance of searching for specific dermoscopic criteria for melanocytic lesions during the examination of a pigmented lesion, despite possible observations of characteristic structures of non-melanocytic lesions, in order to increase the accuracy in the diagnosis of melanoma.